Distributed Control Strategy for Vehicular Networking Channel Congestion - LIU Biao; HU Zhiqiang; WANG Hengyang (Journal of Harbin University of Science and Technology)
The performance of vehicular networking security applications depends on the amount of security information sent by neighboring nodes, and the large number of data packets will cause channel congestion and reduce the efficiency of information propagation. This paper first deduces the parking of vehicles Loose distribution model. On this basis, by solving the data transmission probability and channel busy rate, we can further obtain the probability model of successful packet reception, and consider the hidden terminal problem to amend it. After that, the information delivery rate model was deduced and simulated to verify the validity of the model. Finally, a channel congestion distributed control strategy is designed according to the information delivery rate model. This strategy adjusts the transmission power of each node in real time according to its own environment to keep the information delivery rate near the maximum value, thereby ensuring the transmission efficiency of basic security information. Finally, the effectiveness of the control strategy is verified through simulation experiments. The results show that the designed channel congestion control strategy can maintain the information delivery rate around the maximum value and avoid channel congestion.